1987
DOI: 10.1063/1.98437
|View full text |Cite
|
Sign up to set email alerts
|

Lattice relaxation of pressure-induced deep centers in GaAs:Si

Abstract: Deep centers induced by hydrostatic pressure in GaAs:Si have been studied by deep level transient spectroscopy and constant temperature capacitance transient techniques. The capture behavior of these centers has been studied in detail and found to be consistent with the multi phonon emission theory. The pressure coefficients of the ionization energy and the barrier height are consistent with the large lattice relaxation model proposed by D. V. Lang and R. A. Logan [Phys. Rev. Lett. 39, 635 (977)].Recently Mizu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Furthermore, studies of superlattices indicate a strong link of the centre of the L minimum [20]. On the other hand, an unambiguous conclusion in favour of the model with substantial lattice relaxation, according to negative-U centres [21], was apparently drawn from the different pressure coefficients of the centre and the L band in [8] and also from the pressure dependence of measurements of local vibrational modes [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, studies of superlattices indicate a strong link of the centre of the L minimum [20]. On the other hand, an unambiguous conclusion in favour of the model with substantial lattice relaxation, according to negative-U centres [21], was apparently drawn from the different pressure coefficients of the centre and the L band in [8] and also from the pressure dependence of measurements of local vibrational modes [15].…”
Section: Discussionmentioning
confidence: 99%
“…They can be caused by a shift of the Si atom in the 111 direction to an interstitial site, accompanied by either a substantial lattice relaxation or only a slight lattice relaxation. The metastable centres have been investigated in numerous experiments for thermal equilibrium; see, e.g., [6][7][8][9][10][11][12][13][14][15] concerning GaAs. In the present paper we firstly investigate the field dependence for the charge transfer and find the existence of a threshold field for carrier trapping; secondly, the spectral dependence of the carrier release caused by IR radiation is measured.…”
Section: Introductionmentioning
confidence: 99%
“…The DX centers in bulk semiconductors have been intensively studied for many years especially in the 1980s and 1990s [7][8][9]. Nonetheless, an investigation of DX-centers and the effects on low dimensional systems are still ongoing processes [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Several structures for the DX center have been proposed in the literature, such as the broken-bond model (BB-DX) and the α and β cation-cation bond model (CCB-DX) [18][19][20]23 . In general, DX centers can be stabilized by pushing up the conduction band either by pressure, alloying, or quantum confinement 16,17,24 . For GaAs and other III-V and II-VI semiconductors, calculations have shown that the cation site donor-induced DX centers are easier to form than the anion site donor-induced ones 23,25,26 .…”
Section: Introductionmentioning
confidence: 99%
“…The DX center is an important defect in semiconductors that converts a shallow donor into a deep level [14][15][16][17] . Thus it is a major "killer" defect for the saturation of free-electron carrier concentration in the doping process [18][19][20][21][22] .…”
Section: Introductionmentioning
confidence: 99%